ULAMA DAN PESANTREN DALAM DINAMIKA POLITIK DAN KULTUR NAHDLATUL ULAMA - Wasisto Raharjo Jati (Ulul Albab, 2013)
The article endeavors to trace power relationship between muslim religious leaders (ulama) and islamic boarding school (pesantren) in the political dynamics of Nahdlatul Ulama (NU). Both entity are not only an essential element needed to pressure political and cultural for NU, but also the National Awakening Party (PKB) as a political party for nahdliyyin. The existence of organizational conflicts that occurred in the PKB also influence the dynamics of the NU that resulted fragmentation among ulama and pesantren. The implication is there a divergence of politics and culture among ulama and pesantren in the base region of Central Java and East Java.